Predicting firm failure: A behavioral finance perspective - R. Yazdipour; Richard L. Constand (The Journal of Entrepreneurial Finance (JEF), 2010)
In this article we first argue that researchers in the area of financial distress and failure cannot ignore the human/managerial/decision-making side of the business and just focus on the business' operations side; as has been the case so far for almost all the research in the area. We then discuss how psychological phenomena and principles, known as heuristics or mental shortcuts, could be utilized in building more powerful success/failure prediction models especially for small and medium sized enterprises (SMEs).
Keywords: 650